2019
DOI: 10.1074/jbc.ra119.007925
|View full text |Cite
|
Sign up to set email alerts
|

Human DNA polymerase η has reverse transcriptase activity in cellular environments

Abstract: Edited by Patrick SungClassical DNA and RNA polymerase (pol) enzymes have defined roles with their respective substrates, but several pols have been found to have multiple functions. We reported previously that purified human DNA pol (hpol ) can incorporate both deoxyribonucleoside triphosphates (dNTPs) and ribonucleoside triphosphates (rNTPs) and can use both DNA and RNA as substrates. X-ray crystal structures revealed that two pol residues, Phe-18 and Tyr-92, behave as steric gates to influence sugar selecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
33
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 41 publications
(34 citation statements)
references
References 64 publications
1
33
0
Order By: Relevance
“…Our laboratory has previously shown that hpol η can act as a reverse transcriptase in human cell extracts (38), and here we examined this novel function of hpol η using modified RNA as a template, employing physiological concentrations of dNTPs and rNTPs ( Fig. 3) under in vitro conditions.…”
Section: Hpol η Tolerates the Damaged Ribonucleotide 1n 6 -εRamentioning
confidence: 99%
See 4 more Smart Citations
“…Our laboratory has previously shown that hpol η can act as a reverse transcriptase in human cell extracts (38), and here we examined this novel function of hpol η using modified RNA as a template, employing physiological concentrations of dNTPs and rNTPs ( Fig. 3) under in vitro conditions.…”
Section: Hpol η Tolerates the Damaged Ribonucleotide 1n 6 -εRamentioning
confidence: 99%
“…The TLS process has garnered considerable attention due to the tolerance of damage in DNA in an errorfree or error-prone manner (39,40). TLS also plays an important role in tolerance of ribonucleotides in DNA, and the main key player is hpol η (especially in dealing with lagging strands derived from Okazaki fragments) (16,24,38,(41)(42)(43)(44)(45)(46). Studies with 8-oxo-rG in DNA indicate that hpol η is required for the tolerance of this adduct (24).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations